Boostcharging Li-ion batteries: A challenging new charging concept - Notten, P.H.L.; Veld, J.H.G. Op het; Beek, J.R.G. van (Journal of power sources, 2005)
Boostcharging is proposed as a new, ultra-fast, recharging algorithm for Li-ion batteries. Characteristic for boostcharging is that close-to-fully discharged batteries can be recharged with very high currents for a short period of time. Cycle life of Li-ion batteries, boostcharged and additionally standard charged to full capacity do not introduce any negative degradation effects. Boostcharging is shown to be very rapid. For example, a fully discharged battery can be recharged within 5 min to one-third of its rated capacity.